2013
DOI: 10.1177/0004563213503819
|View full text |Cite
|
Sign up to set email alerts
|

A review of pancreatic cyst fluid analysis in the differential diagnosis of pancreatic cyst lesions

Abstract: Diagnosis and management of pancreatic cyst lesions is challenging as there is currently no investigation that offers both high diagnostic sensitivity and high specificity for the identification of potentially malignant lesions. Accurate classification of these lesions is vital in order to avoid unnecessary treatment of benign lesions and missed opportunities for early treatment of lesions that are malignant/pre-malignant. Pancreatic cyst fluid analysis has an important role in diagnosis, although all currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 90 publications
0
19
0
4
Order By: Relevance
“…Computer tomography (CT) and magnetic resonance imaging (MRI) are unable to accurately distinguish between benign and malignant pancreatic cystic lesions [4] and therefore the majority of patients undergo an endoscopic ultrasound scan (EUS) and fine needle aspiration (FNA) for cytology and cystic fluid analysis. EUS can differentiate between benign, pre-malignant and malignant lesions with an accuracy ranging from 40 to 93% [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Computer tomography (CT) and magnetic resonance imaging (MRI) are unable to accurately distinguish between benign and malignant pancreatic cystic lesions [4] and therefore the majority of patients undergo an endoscopic ultrasound scan (EUS) and fine needle aspiration (FNA) for cytology and cystic fluid analysis. EUS can differentiate between benign, pre-malignant and malignant lesions with an accuracy ranging from 40 to 93% [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Because some pancreatic cysts are precancerous, and because pancreatic cancer is such a deadly condition, diagnosing the type of pancreatic cyst lesion accurately is a high stakes challenge. Despite the recent improvements in CT and MRI methodologies, these imaging approaches are unable to distinguish cancerous, premalignant and benign cysts reliably, in part due to a lack of sensitivity to cellular structure and biochemical properties, with wide variations in the reported accuracy ranging from 20% to 80% 37 . EUS is still the most sensitive technique currently available for the detection of small (<2–3 cm) pancreatic cysts 38,39 , however, the accuracy of EUS for distinguishing mucinous from non-mucinous cysts is only 51% 6 .…”
Section: Discussionmentioning
confidence: 99%
“…This study hypothesized that the increase of viscosity is the result of higher glycoprotein or mucin expression. Further studies analysing pancreatic fluid cysts have shown that many transmembrane proteins and mucinous columnar cells are sloughed with higher grades of dysplasia, which may also impact viscosity, 20 a fact which is currently under evaluation for predicting malignant potential in cystic pancreatic neoplasms using diffusionweighted imaging. 21 Therefore, inference may be drawn that CBD dilation occurs owing to increased viscosity of the pancreatic fluid and the change of the fluid dynamics.…”
Section: Discussionmentioning
confidence: 99%